2020
DOI: 10.1007/s40626-020-00188-5
|View full text |Cite
|
Sign up to set email alerts
|

Foliar-applied glycine betaine minimizes drought stress-related impact to gas exchange and the photochemical efficiency of PSII in sugarcane

Abstract: Sugarcane is one of the most important crops in the world, but subject to yield losses caused by sporadic droughts during the growing season. To mitigate the effects of drought stress, different strategies have already been used, including the foliar application of glycine betaine (GB). Thus, the present study aimed to evaluate the effect of GB spraying via leaf on gas exchange, chlorophyll fluorescence and on the sugarcane water status subjected to drought stress and rewatering. The experiment was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…For example, Verma et al [29] found that the foliar application of silicon, in addition to reducing the harmful effects of water deficit in sugarcane, also improves the plant's antioxidant defense system, by favoring the synthesis of photosynthetic pigments and the maximum quantum efficiency of photosystem II. In another study, Maia Júnior et al [37] observed that, in sugarcane plants, the foliar application of glycine betaine mitigates the harmful effects of water deficit on the PSII photochemical apparatus.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Verma et al [29] found that the foliar application of silicon, in addition to reducing the harmful effects of water deficit in sugarcane, also improves the plant's antioxidant defense system, by favoring the synthesis of photosynthetic pigments and the maximum quantum efficiency of photosystem II. In another study, Maia Júnior et al [37] observed that, in sugarcane plants, the foliar application of glycine betaine mitigates the harmful effects of water deficit on the PSII photochemical apparatus.…”
Section: Resultsmentioning
confidence: 97%
“…2020). Exogenous application of glycine betaine improves the rate of photosynthesis and induces drought tolerance in Saccharum officinarum (de Oliveira Maia Júnior et al . 2020).…”
Section: Production Of Osmolytesmentioning
confidence: 99%
“…It is normally used to increase tolerance against abiotic stresses, such as freezing, salinity and drought stress [18]. Foliar application of GB results in rapid uptake, translocating to different plant organs [18], enhancing antioxidant defence [19,20], leaf gas-exchange attributes [21,22] and growth under stress conditions [22]. A recent publication shows how a foliar application of 11.5 g L −1 can increase yield [23].…”
Section: Introductionmentioning
confidence: 99%